Effects of freeze-thaw pretreatments on the drying characteristics, physicochemical and phytochemical composition of red dragon fruit during mid- and near-infrared drying. Issue 4 (6th March 2023) - Bassey, Edidiong Joseph; Sun, Da-Wen; Esua, Okon Johnson; Cheng, Jun-Hu
Abstract: Effects of freeze-thaw pretreatments using slow (SFZ), fast (FFZ) and ultrafast (UFZ) freezing on the drying characteristics, physicochemical and phytochemical compositions of red dragon fruit slices were investigated during mid- (MIR) and near-infrared (NIR) drying. Results indicated that the pretreatments altered cellular structure, reduced drying time and increased drying rates and effective moisture diffusivity, and these effects were dependent on the freezing methods, showing that FFZ and UFZ could improve physicochemical quality, ascorbic acid, and hydroxyl scavenging ability, while SFZ could enhance total phenolics and flavonoid contents, betalains, and ABTS radical scavenging activity. Overall, freeze-thaw pretreatments prompted more efficient drying due to structural modification and improved heating uniformity, they also presented undesirable effects on color, shrinkage, betalains, phenolics and ABTS scavenging activity. The study provided a theoretical basis for applying freeze-thaw pretreatments during infrared drying and indicated the need for optimization studies for improving drying efficiency.